Effect of cold-restraint stress on glutathione and lipid peroxide levels in the liver and glandular stomach of rats - YALÇIN, AHMET SUHA; YEGEN, BERRAK (My University, 1990)
The effect of starvation and cold-restraint stress on glutathione and lipid peroxide levels in the liver, stomach and plasma of rats was investigated. Hepatic and gastric glutathione levels were significantly decreased in starvation and cold-restraint groups when compared with values obtained from the control group. In both tissues, lipid peroxide levels were significantly decreased after starvation but were not significantly different from control values after cold-restraint treatment. However, when compared with the values obtained from the starvation group there was a significant increase in both hepatic and gastric lipid peroxide levels after cold-restraint. Plasma lipid peroxide levels were slightly decreased in the starvation group and significantly increased in the cold-restraint group. Our results suggest that pathological consequences of stress on different tissues could be due to stimulation of lipid peroxidation.
Keywords: Animals; Rats; Glutathione; Liver; Gastric Mucosa; Stomach; Cold Temperature; Lipid Peroxides; Rats, Inbred Strains; Starvation